The Effect Of Accounting System Effectiveness And Accountant Expertise On The Quality Of Financial Reports With The Use Of Accurate Software As A Moderating Variable At Pt Global Danapati Niaga (Blibli Omg) - Tengku Sheila Chairunisa; Renny Maisyarah; M. Irsan Nasution (Journal of Research in Social Science and Humanities, 2026)
This study aims to analyze the effect of accounting system effectiveness and accountant competence on the quality of financial reports, as well as to test the role of Accurate software as a moderating variable at PT Global Danapati Niaga (Blibli OMG). The research method uses a survey-based quantitative approach, with data processing through multiple linear regression and Moderated Regression Analysis (MRA). The results show that accounting system effectiveness is proven to contribute positively and significantly to the quality of financial reports, indicated by a coefficient of 0.29 with a significance of 0.000. Accountant competence also has a positive and significant effect, with a coefficient of 0.34 and a significance of 0.000. These findings strengthen that system capabilities and human resource expertise are the main foundations in producing quality reports. Moderation analysis reveals that Accurate software is also able to strengthen the relationship between accounting system effectiveness and accountant competence with the quality of financial reports. This is reflected in the significance value of the X1×Z interaction of 0.007 and X2×Z of 0.006. Simultaneously, the research model remains valid and significant (F = 6.234; p = 0.006), confirming that both independent variables are important determinants in improving the quality of financial reporting. Overall, this study emphasizes that companies need to prioritize strengthening accounting systems and developing accountant competencies as key strategies in improving the quality of financial reporting. Meanwhile, the use of Accurate software is more appropriately positioned as an operational support tool, rather than as a factor capable of strengthening the relationship between the main research variables.